Protocol for detecting introgressed archaic variants with SPrime - Zhou, Ying (STAR Protoc, 2021)
The SPrime program detects the variants in current-day populations that were introgressed from an archaic source in the past. It is optimized for detecting introgression from Neanderthals and Denisovans in modern humans. We provide a protocol for detecting Neanderthal and Denisovan introgression in 1000 Genomes Project data, specifically focusing on the CHB (Han Chinese in Beijing) population. For complete details on the use and execution of this protocol, please refer to Browning et al. (2018).